Expanding the Regulon of the Bradyrhizobium diazoefficiens NnrR Transcription Factor: New Insights Into the Denitrification Pathway - Jiménez-Leiva, Andrea; Cabrera, Juan J.; Bueno, Emilio; Torres, María J.; Salazar, Sergio; Bedmar, Eulogio J.; Delgado, María J.; Mesa, Socorro (Frontiers in Microbiology, 2019)
Denitrification in the soybean endosymbiont Bradyrhizobium diazoefficiens is controlled by a complex regulatory network composed of two hierarchical cascades, FixLJ-FixK2-NnrR and RegSR-NifA. In the former cascade, the CRP/FNR-type transcription factors FixK2 and NnrR exert disparate control on expression of core denitrifying systems encoded by napEDABC, nirK, norCBQD, and nosRZDFYLX genes in response to microoxia and nitrogen oxides, respectively. To identify additional genes controlled by NnrR and involved in the denitrification process in B. diazoefficiens, we compared the transcriptional profile of an nnrR mutant with that of the wild type, both grown under anoxic denitrifying conditions. This approach revealed more than 170 genes were simultaneously induced in the wild type and under the positive control of NnrR. Among them, we found the cycA gene which codes for the c550 soluble cytochrome (CycA), previously identified as an intermediate electron donor between the bc1 complex and the denitrifying nitrite reductase NirK. Here, we demonstrated that CycA is also required for nitrous oxide reductase activity. However, mutation in cycA neither affected nosZ gene expression nor NosZ protein steady-state levels. Furthermore, cycA, nnrR and its proximal divergently oriented nnrS gene, are direct targets for FixK2 as determined by in vitro transcription activation assays. The dependence of cycA expression on FixK2 and NnrR in anoxic denitrifying conditions was validated at transcriptional level, determined by quantitative PCR, and at the level of protein by performing heme c-staining of soluble cytochromes. Thus, this study expands the regulon of NnrR and demonstrates the role of CycA in the activity of the nitrous oxide reductase, the key enzyme for nitrous oxide mitigation.